Self-assembled nanostructured cellulose prepared by a dissolution and regeneration process using phosphoric acid as a solvent. (5th June 2015) - Hao, Xiaoxia; Shen, Wei; Chen, Zhigang; Zhu, Jiaming; Feng, Li; Wu, Zongwei; Wang, Peng; Zeng, Xiaoxiong; Wu, Tao
Highlights: Nanostructured celluloses were prepared by a dissolution and regeneration process. Cold phosphoric acid is used to dissolve the native crystalline celluloses. Regeneration in water led to the self assembly of nanostructured celluloses. Cellulose nanofibers or nanospheres can be obtained at varied conditions. Abstract: This report describes a "green" method for preparing self-assembled nanostructured cellulose through a dissolution and regeneration process. Cold phosphoric acid is used to dissolve cellulose in order to convert crystalline cellulose into its molecular form. Self-assembly of cellulose molecules into nanostructured cellulose is achieved by using water to regenerate cellulose. By controlling the temperature and time of the phosphoric acid treatment between dissolution and regeneration, the degree of polymerization and the degree of substitution of phosphorous for the regenerated celluloses can be tuned. As a result, cellulose nanofibers or nanospheres can be obtained when the treatment temperature is set to 5 or 50 °C, respectively. X-ray analysis shows that the cellulose nanofibers are amorphous and that the cellulose nanospheres are structured similarly to cellulose II with crystallinity indexes between 56 and 73%. Our method offers a "green" process for preparing nanostructured celluloses in high yields.